2019
DOI: 10.1108/jfbm-04-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Better with age: financial reporting quality in family firms

Abstract: Purpose The purpose of this paper is to contribute to the literature on financial reporting quality (FRQ) within family firms (FFs), assessing whether longevity can determine a different propensity to earning management (EM) behaviors. Design/methodology/approach The sample, composed by Italian and Brazilian listed family (and non-family) firms, is segregated into old and young. For each subsample, unsigned discretionary accruals are calculated, using two different EM models. A linear regression model is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Other researchers also observed a positive effect of the ownership structure on firm performance [50]. Additionally, the ownership structure positively affected financial reporting quality [51]. The correlation between financial reporting quality and ownership structure has been studied in many types of research.…”
Section: Theoretical Background 21 Creative Accounting Determinants A...mentioning
confidence: 98%
“…Other researchers also observed a positive effect of the ownership structure on firm performance [50]. Additionally, the ownership structure positively affected financial reporting quality [51]. The correlation between financial reporting quality and ownership structure has been studied in many types of research.…”
Section: Theoretical Background 21 Creative Accounting Determinants A...mentioning
confidence: 98%
“…Figure 2 shows the geographical distribution of sample data. According to this distribution, the majority of studies were conducted at the country level, with 11 being cross-country studies (e.g., Attig et al, 2020;Tommasetti et al, 2020;S aenz Gonz alez and Garc ıa-Meca, 2014). Cross-country studies offer a more in-depth understanding of the relationship, compared to a single-country perspective.…”
Section: Geographical Distributionmentioning
confidence: 99%
“…The agency theory suggested that managers, who represent shareholders often indulge in creative accounting practices to maximize shareholder wealth. This theory stated that control mechanisms need to be carried out for protection of the shareholders against any conflict that affects their profit (Tommasetti et al 2019). Hence, an information asymmetry is noted due to the profit conflicts occurring between the shareholders and managers.…”
Section: Creative Accounting Determinants and Financial Reporting Qua...mentioning
confidence: 99%